Housing at Risk of Collapse and its Effects on the Health Situation of Residents and Management Policies: The Case of the Old City of Salé in Morocco - Arabi, Nezha; Aneflouss, Mohamed (Journal of Humanities & Social Sciences, 2025)
The phenomenon of the housing threatened with collapse presents various challenges on urban, social, environmental, and public health levels, particularly in the old city of Sale. This study aims to examine the characteristics of the housing threatened with collapse and the factors contributing to its deterioration in the old city of Sale, as well as to assess the health conditions of its inhabitants. The study also highlights state policies for managing, addressing, and combating this type of housing in the studied area, utilizing data gathered from the field study conducted in the Sale prefecture and the Prince Moulay Abdallah Provincial Hospital in Sale. The study concludes that this type of housing is linked to several interconnected factors, most notably the population increase in the city, the socio-economic vulnerability of residents, the aging of buildings, and the limited effectiveness of successive housing policies. As a result, this issue remains a constant concern for public authorities seeking effective and efficient solutions to address its conditions and ensure the safety of residents, while providing housing that meets public health standards. Therefore, the phenomenon of the housing threatened with collapse requires an urgent response, including recommendations such as evaluating the condition of buildings, developing rehabilitation plans using sustainable building techniques, providing appropriate funding and support for affected families, and updating regulations to ensure the implementation of modern engineering standards. Additionally, enhancing collaboration with various organizations and bodies is essential to increase public awareness and implement joint projects to improve housing conditions.